(untitled) (Scientific journal of the Fergana State University, 2026)
Today, the increasing demand for food and the use of synthetic pharmaceutical chemical compounds in the agricultural production of fruits and vegetables are causing a growing number of negative changes in public health and the soil environment. Metabolites produced by Trichoderma species serve as a sustainable alternative for controlling plant diseases and mitigating harmful substances released by fungi. As part of this study, we presented a literature review of several metabolites concerning Trichoderma spp regarding the biologic activity and isolated some secondary metabolites concerning T. asperellum and described their activity. We summarize and group various antifungal secondary metabolites of Trichoderma spp. We consider in full detail some aspects concerning phytopathogenic fungi, their chemistry and biosynthesis. For the isolation of metabolites, thin-layer chromatography was performed for detection using columnar chromatography and the obtained substances were investigated by GS-MS analysis. As a result, it was found that the chloroform:methanol (5:1) system is characterized by a number of substances that differ from the metabolites that are separated from the other solvent system.